O ensino de história da educação física no curso de Educação Física do Espírito Santo (1931-1939) - Will, Thiago Ferraz (2017)
It seeks to understand the teaching of the discipline History of Physical Education at the Physical Education School of Espirito Santo. It aims to understand how History of Physical Education was taught in the 1930s, and how the knowledge of this discipline was absorbed by the students and materialized in their monographs. As a theoretical methodological reference, it uses the concepts of representational struggles (CHARTIER, 1990), strategy and tactics (CERTEAU, 1994), makes use of documentary criticism (BLOCH, 2001). As sources, we use the programs of the discipline Physical Education History, the documents of the Permanent Archive of the CEFD/Ufes and the monographs produced between the years of 1932 to 1939. The teaching of history of physical education is one of the most recurrent subjects in the curriculum, because it stands out as being the assessment of the evolutionary history of physical education, on the other hand, the teaching of history of physical education in the 1930 had a different connotation, because it was through history that the attempt was made to legitimize the French Gymnastics Method as the ideal method for Brazilian specificities, reflecting this approach in the elaboration of student monographs with a reproduction of a discourse that sought to become hegemonic.